Effect of hydrogen-peroxide-mediated oxidative stress on human dental pulp cells - Soares, Diana Gabriela de Souza [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza[UNESP] (Elsevier, 2015)
To evaluate the effect of the oxidative stress on human dental pulp cells (HDPCs) promoted by toxic concentrations of hydrogen peroxide (H2O2) on its odontoblastic differentiation capability through time. Methods HDPCs were exposed to two different concentrations of H2O2 (0.1 and 0.3 μg/ml) for 30 min. Thereafter, cell viability (MTT assay) and oxidative stress generation (H2DCFDA fluorescence assay) were immediately evaluated. Data were compared with those for alkaline phosphatase (ALP) activity (thymolphthalein assay) and mineralized nodule deposition (alizarin red) by HDPCs cultured for 7 days in osteogenic medium. Results A significant reduction in cell viability and oxidative stress generation occurred in the H2O2-treated cells when compared with negative controls (no treatment), in a concentration-dependent fashion. Seven days after H2O2 treatment, the cells showed significant reduction in ALP activity compared with negative control and no mineralized nodule deposition. Conclusion Both concentrations of H2O2 were toxic to the cells, causing intense cellular oxidative stress, which interfered with the odontogenic differentiation capability of the HDPCs. Clinical significance The intense oxidative stress on HDPCs mediated by H2O2 at toxic concentrations promotes intense reduction on odontoblastic differentiation capability in a 7-day evaluation period, which may alter the initial pulp healing capability in the in vivo situation.
Keywords: Pulp cells; Hydrogen peroxide